Analysis Of Different Power Levels, Difficulty, And Effectiveness of Distracting Final Semester Assessment Questions (PAS) For Arabic Language Class VIII MTs Irsyadul Athfal - Dahlan, Ahmad Zaini; Shidiq, Fauzie Muhammad; Anwar, Zaky; Al Haqiqy, Muhammad Syihabul Ihsan; Qomari, Nur (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This study aims to determine the quality of the final exam items of Arabic language subjects in the 2023 academic year at MTs Irsyadul Athfal Gresik regarding the level of differentiation, difficulty, and effectiveness of exemptions. This research is an evaluation research with a quantitative descriptive approach. The research was conducted with a sample of 13 student answer sheets. The data collection technique used was the documentation technique. The results of this study indicate that (1) based on the criteria of differential power obtained 11 questions with inferior interpretation, 21 questions with poor interpretation, 1 with moderate interpretation, 9 with good interpretation, and 3 with very good interpretation. (2) based on the difficulty level criteria, 15% of the items were very difficult, 4% of the items were categorized as difficult, 2% of the items were moderate, 13% of the items were categorized as easy, and 64% of the items were very easy. (3) based on the effectiveness of the check obtained 1 item (2.22%) has a very good checker, then 34 items (75.55%) have a good enough checker or revised, and 10 items (22.22) that must be replaced because the checker does not work or rejected. The implication of this research is to inform the results of the analysis of the question items to be used as a comparison material for the test scores of Arabic language tests. Keywords: Distinguishing power; Difficulty; Examination.